China's increasing inequality of wealth: Piketty with Chinese characteristics? - Knight, J; Shi, L; Haiyuan, W (University of Oxford, 2018)
John Knight, LI Shi and WAN Haiyuan The inequality of wealth in China has increased rapidly in recent years. China presents a fascinating case study of how inequality of household wealth increases as economic reform takes place, marketisation occurs, and capital accumulates. Wealth inequality and its growth are measured and decomposed using data from two national sample surveys of the China Household Income Project (CHIP) relating to 2002 and 2013. An attempt is made to explain the rising wealth inequality in terms of the relationships between income and wealth, differential saving, house price inflation, and income from wealth. This last relationship is stressed by Thomas Piketty in his 2014 book. In China the evidence for it is weak, but there is support for a reformulation that includes real capital gain as part of income. Piketty's mechanism is relevant, but only 'with Chinese characteristics'.